2006
DOI: 10.1002/qua.21183
|View full text |Cite
|
Sign up to set email alerts
|

From anisole to 1,2,4,5‐tetramethoxybenzene: Theoretical study of the factors that determine the conformation of methoxy groups on a benzene ring

Abstract: Unhindered ortho-dimethoxy-substituted phenyl rings often display a coplanar conformation. A theoretical study of a series of methoxybenzenes consisting of methoxybenzene (anisole), the three dimethoxybenzenes, and 1,2,4,5tetramethoxybenzene, at the DFT/B3LYP/6-311ϩϩG** level of theory, allows us to identify the factors influencing the conformational preference and attribute the coplanarity of such methoxy groups to mesomeric effects.As the number of methoxy groups in the molecule increases, the number of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Since the benzenoid ring is important for inhibitory activity, the role of the dimethoxy substituents on this ring should be questioned. Desmethoxyquinazoline derivatives ( 34–37 ) were found to be far less active against G9a, which is in agreement with a recent report on related analogues, 35 42 and demonstrates that these substituents are also of importance. A number of theoretical and experimental studies have shown that ortho -dimethoxybenzenes prefer to adopt a co-planar conformation, with the sp 2 oxygen lone pairs projecting towards each other and the corresponding methyl groups angled away from each other.…”
Section: Resultssupporting
confidence: 90%
“…Since the benzenoid ring is important for inhibitory activity, the role of the dimethoxy substituents on this ring should be questioned. Desmethoxyquinazoline derivatives ( 34–37 ) were found to be far less active against G9a, which is in agreement with a recent report on related analogues, 35 42 and demonstrates that these substituents are also of importance. A number of theoretical and experimental studies have shown that ortho -dimethoxybenzenes prefer to adopt a co-planar conformation, with the sp 2 oxygen lone pairs projecting towards each other and the corresponding methyl groups angled away from each other.…”
Section: Resultssupporting
confidence: 90%
“…A likely reason for these observations is that the electronic coupling of tmb to its neighboring p-xylene bridge units is exceptionally weak. The four-fold methoxy-substituted tmb moiety is sterically much more demanding than the xylene or dmb units, 29 a fact that becomes manifest also in low yields obtained for the C-C coupling reactions that involve the tmb building block (see ESIw). A larger equilibrium torsion angle between tmb and p-xylene compared to the respective angles in dmb-xy and xy-xy contacts will lead to (locally) weaker electronic coupling (locally smaller h bb ), [30][31][32][33] a fact that does not reflect from the simple (reduction potential) diagram of Scheme 3.…”
mentioning
confidence: 99%
“…Indeed, both the T g and T max transition temperatures of P6-azo-OC6H13 are much higher. Compared with P6-azo-C6H13, the presence of the oxygen group in P6-azo-OC6H13 may, via a mesomeric effect with the azobenzene group, lead to a higher rigidity of the substituent [26,27]. This loss of flexibility may explain the observed increase in both T g and T max .…”
Section: Influence Of the Substituent Naturementioning
confidence: 96%